Sub genome anchored physical frameworks of the allotetraploid Upland cotton (Gossypium hirsutum L.) genome, and an approach toward reference-grade assemblies of polyploids - Christopher A. Saski (Nature Portfolio, 2017)
Abstract Like those of many agricultural crops, the cultivated cotton is an allotetraploid and has a large genome (~2.5 gigabase pairs). The two sub genomes, A and D, are highly similar but unequally sized and repeat-rich, which pose significant challenges for accurate genome reconstruction using standard approaches. Here we report the development of BAC libraries, sub genome specific physical maps, and a new-generation sequencing approach that will lead to a reference-grade genome assembly for Upland cotton. Three BAC libraries were constructed, fingerprinted, and integrated with BAC-end sequences (BES) to produce a de novo whole-genome physical map. The BAC map was partitioned by sub genomes through alignment to the diploid progenitor D-genome reference sequence with densely spaced BES anchor points and computational filtering. The physical maps were validated with FISH and genetic mapping of SNP markers derived from BES. Two pairs of homeologous chromosomes, A11/D11 and A12/D12, were used to assess multiplex sequencing approaches for completeness and scalability. The results represent the first sub genome anchored physical maps of Upland cotton, and a new-generation approach to the whole-genome sequencing, which will lead to the reference-grade assembly of allopolyploid cotton and serve as a general strategy for sequencing other polyploid species.